Pengaruh Set Kesempatan Investasi, Konservatisme dan Pertumbuhan Laba Terhadap Kualitas Laba Pada Perusahaan Manufaktur Di Indonesia - Elan Kurniawan; Siti Nur Aisah (AKRUAL : Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this study is to obtain empirical evidence about the problem under study, namely "Effect of Set of Investment Opportunities, Conservatism and Profit Growth on Profit Quality in Manufacturing Companies Listed on the Stock Exchange for the Period of 2012-2016". The number of companies sampled in this study were 124 companies. Determination of samples in this study using purposive sampling technique. Testing the hypothesis in this study uses the method of multiple linear regression analysis using the SPSS 22 program. The results show that the investment opportunity set has a significant positive effect on earnings quality, conservatism has a negative but significant effect on earnings quality. And profit growth has a significant positive effect on earnings quality